1981
DOI: 10.1097/00132586-198110000-00055
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Surgical Patients with Verified Preoperative Myocardial Infarction

Abstract: A series of 89 surgical patients (1 11 operations) with preoperative myocardial infarction (MI) was analysed for factors predisposing to the development of a postoperative reinfarction. Six of them suffered postoperative MI, and three of these patients died. In the statistical analysis the following risk factors emerged: age over 60 years, anaemia, hypertension, and the fact that the previous MI had been posterior. Abdominal operations were more dangerous concerning reinfarction than other operations. In the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Patients with coronary disease undergoing cardiac surgery are at higher risk of myocardial infarction if prolonged hypotension occurs during the procedure (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with coronary disease undergoing cardiac surgery are at higher risk of myocardial infarction if prolonged hypotension occurs during the procedure (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…This was also confirmed by Steen et al and Eerola et at. in patients with previous MI [2,15]. There was no relation to the type of anesthetic used to the cardiac complications.…”
Section: Complications Of Vascular Surgerymentioning
confidence: 79%
“…Conversely, there were several studies in which a MI less than six months before operation was not a predictor of perioperative cardiac events. The time elapsed since the MI was not a significant factor in a study by Eerola et al, in which 89 patients underwent 111 operations; 29 operations were in patients with previous MI within 6 months [15]. Foster et al did not find that history of prior MI, including one within six months of the noncardiac procedure, had a statistically significant independent association with operative mortality or cardiac morbidity [16].…”
Section: Complications Of Vascular Surgerymentioning
confidence: 96%
“…This has also been identified as a risk factor [26,36,40,80]. In addition, Pasternak and colleagues [75] found a higher infarction rate in patients with a low preoperative ejection fraction (less than 35%).…”
Section: Other Factors Relevant To Coronary Artery Disease Congestivementioning
confidence: 96%
“…Steen, Tinker and Tarhan [94] found no significant correlation between the PMI rate and the site of a previous MI. On the other hand, Eerola and colleagues [36] found that a previous posterior infarction was a significant risk factor, while Arkins, Smessaert and Hicks [3] found lower mortality rates if earlier infarction was subendocardial.…”
Section: Site Of Previous MImentioning
confidence: 97%